Palynofacies, palaeoenvironmental change and sequence stratigraphy of the Middle Jurassic, Cleveland basin and Brent group of UK - Ross, C (1999)
Palynofacies analysis, which is the study of microscopic organic matter can, in association with sedimentolog- ical and palaeoecological data, provide temporal and spatial resolution in the characterisation of sedimentary environments and potentially, vegetation and climate. However, the reliability of palynofacies analysis as a tool for environmental reconstruction has been questioned recently. This uncertainty is due a number of factors, including the lack of standardisation in the processing and counting of organic matter, subjective and vague terminology used to classify organic matter, and existence of numerous classification schemes. These have all restricted comparison between studies and hence hampered the advance of palynofacies analysis. The most important factor is, however, limited understanding of the controls which govern the genesis of particular associations of particulate organic matter. These issues were addressed using a two-fold approach. Firstly, the particulate organic matter classification scheme created by Lewis in 1995 was tailored to produce a robust hierarchical classification scheme. Secondly, multivariate statistical analysis was applied to a Middle Jurassic data set. This revealed that the primary control upon the nature of the organic matter associations is preservation potential which is affected by redox status, and to a lesser extent by the degree and duration of transportation and disturbance to which the organic-matter has been subjected. The secondary influence was determined to be a change in the nature of organic matter through time. Following this analysis 19 different organic-matter assemblage groups were defined to decipher palaeoenvironmental changes during the Middle Jurassic. Variations in the associations of organic matter through the Aalenian to Bathonian reflect changes in the redox status, proximity to source, salinity and hydrodynamics. This investigation suggests that aridity and/or pronounced seasonality commenced during the early Bajocian of the region which is earlier than the findings of previous investigations. This is based principally on the concomitant increase in black fragments (charcoal) and acme of Classopollis pollen in both the Cleveland Basin and Brent Group. The black fragments are probably charcoal rather than post-depositionally altered fragments because they occur in a range of oxic and anoxic environments, in conjunction with brown fragments, and in a range of lithofacies. These results not only permit the characterisation of the environment of deposition but also illustrate that palynofacies yields a discernible climatic signal.